Higher Education Polytechnic Institutes as an Alternative to the Creation of New Universities in the 1970s in Argentina - Mendonça, Mariana (CIAN-Revista de Historia de las Universidades, 2020)
Post-secondary education has become one of the most important issues on the global political agenda since the beginning of the Second World War. The increase in demand at this level generated institutional growth that in turn led to a process of diversification and differentiation that has intensified over the last few decades, and has taken different forms in each country. Public and private universities and non-university institutions, are just some of the many types of academic units that exist throughout the world. Argentina is an emblematic case of this process, since the enrolment and institutional expansion took place mainly in the public university sector. In spite of this, there were different projects that were presented since the mid-twentieth century, which proposed the implementation of models similar to those in other countries. In this work we aim to analyze the proposal of the rector of the National University of Cuyo, formulated in 1972, and which suggested the implementation of Higher Education Polytechnic Institutions. This is a relevant project since, despite the fact that the expansion of the university system ended up taking on a completely different form, its analysis allows us to shed light on the debates that gave form to this expansion process.
Keywords: university; policies; higher education; diversification; differentiation